Foreign language requirements in the world of work : results of the 2006, 2012 and 2018 BIBB/BAuA Employment Surveys - Hall, Anja [Verfasser] (My University, 2021)
"Knowledge of foreign languages is becoming increasingly important in working life in light of economic globalisation and international interconnectedness. This article uses the 2006, 2012 and 2018 BIBB/BAuA Employment Surveys to show the importance attached to knowledge of foreign languages in today’s world of work, to highlight how these requirements have developed over time, and to identify the occupations in which such knowledge plays a particularly major role." (author's abstract; BIBB-Doku)
Fremdsprachenanforderungen in der Arbeitswelt : Ergebnisse der BIBB/BAuA-Erwerbstätigenbefragungen 2006, 2012 und 2018
Keywords: G 1.2.3.1 Potenziale; 370; BIBB-/BAuA-Erhebung; Sprachkenntnisse; Fremdsprachenerwerb; Berufsanforderung; Schlüsselqualifikation